Arch replacement with collared elephant trunks: The Siena approachCentral MessagePerspective - Eugenio Neri, MD; Luigi Muzzi, MD; Enrico Tucci, MD; Marco Cini, MD; Lucio Barabesi, DrPh; Giulio Tommasino, MD; Carmelo Ricci, MD (JTCVS Techniques)
Objective: To illustrate our experience and results in patients with diffuse aneurysmal disease treated with arch replacement using the Siena collared graft, a device designed in 2002 to improve the elephant trunk technique. Results of the first step surgical implant and the subsequent treatment strategies, with extensive use of endovascular techniques, are reported. Methods: All aortic arch–replacement procedures using the Siena graft between February 2002 and January 2020 were retrospectively analyzed for early and late clinical outcomes. Results: Of 146 patients (54 women, 36.9%) with a median age of 69.1 years (interquartile range 58.4-75.0 years), 55 (37.6%) had acute/chronic dissection with false lumen aneurysmal dilatation, 91 (62.3%) had degenerative aneurysms, 45 (30.8%) were redo operations, and 14 (9.5%) had connective tissue disease. First-stage outcomes: 10.9% 30-day mortality (n = 16); 5.4% stroke (n = 8, 6 disabling, 2 nondisabling; 3 fatal); and 0.6% paraplegia. Outcomes for 113 second-stage procedures (77.3%, n = 97 endovascular [66.4%], n = 16 surgical [10.9%]) were 5.3% and 8.8% 30-day and 180-day mortality; no stroke; 10.6% paraplegia. Median follow-up was 5.7 years (range: 0-18.02 years) median survival was 16.65 years (95% lower confidence limit, 10.06 years) with no significant difference between aneurysm and dissection patients. Freedom from further treatment was 87.0% (95% confidence interval, 79.9%-94.7%) at 5 years and 71.4% (95% confidence interval, 71.4%-84.7%) at 10 years; median time to reintervention was 2.59 years (interquartile range, 0.52-5.20 years) with no difference (P = .22) between dissection and aneurysm groups. Conclusions: Siena collared graft represents a reliable platform for the treatment of diffuse aneurysmal disease. This device offers the flexibility required in the treatment of extended aortic lesions and guarantees the choice of the most appropriate approach for treatment completion. In this context, the availability of hybrid grafts has not modified the role of this device in arch surgery.